A Study of the Factors that Influence Stock Investment Decisions Among Young People in West Jakarta, With a Focus on Financial Literacy, Financial Behaviour, Risk Tolerance and Income - Retno Puji Astuti; Nurhasanah Nurhasanah (Electronic Journal of Education, Social Economics and Technology, 2026)
This study is motivated by the significant growth of millennial investors in the Indonesian capital market, which is accompanied by low levels of financial literacy. Given the increasingly important role of millennial investors in the economy, it is crucial to understand the factors that influence their stock investment decisions. The study aims to analyse the influence of financial literacy, financial behaviour, risk tolerance and income on stock investment decisions among millennial investors in West Jakarta. A quantitative approach was employed to address this issue, utilising primary data obtained through a survey of millennial investors. The study population was young people in West Jakarta. The sample size was 100 respondents. Regression analysis was conducted using Smart PLS version 4.1.09. The research method and data analysis used were SEM-PLS. The results of the study suggest that financial literacy, financial behaviour and income do not influence investment decisions. However, risk tolerance was found to have a positive and significant influence on investment decisions.